Acoustic echo cancellation using iterative-maximal-length correlation and double-talk detection. - Jang-Chyuan Jenq (IEEE Transactions on speech and audio processing)
The conventional maximal-length-correlation (MLC) algorithm to estimate room impulse response for adaptive echo cancellation (AEC) is disturbed by both far-end and near-end speech. In this paper, a new iterative-maximal-length-correlation (IMLC) algorithm is proposed to reduce the far-end speech interference. To avoid the near-end interference, a new double-talk detection (DTD) method is proposed by tracking the squared coefficients errors of the AEC filter. This DTD method has well-separated detection margins among single-talk (ST), double-talk (DT), and echo path changes. Statistical analysis and computer simulations confirm that our proposed IMLC-DTD algorithm outperforms conventional methods